2001
DOI: 10.1080/02508060108686930
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Latest Research Findings on Causes of Groundwater Arsenic Contamination in Bangladesh

Abstract: The groundwater arsenic contamination problem in Bangladesh is the worst in the world. Two hypotheses are prevailing as the cause (mobilization) of groundwater arsenic contamination in Bangladesh. One is called "pyrite oxidation" and the other is "oxy-hydroxide reduction." According to the first hypothesis, groundwater arsenic contamination is human-made, which has a relationship with excessive groundwater withdrawal. On the other hand, according to the second one, the contamination is natural. The British Geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 1 publication
1
20
0
Order By: Relevance
“…Time here is seen to be linked with arsenic also indicate the oxidative dissolution of arsenic mineral which may again be consider to release of arsenic in ground water as a time variable parameter. The same phenomenon is endorsed by Fazal et al (2001).…”
Section: Hierarchical Cluster Analysissupporting
confidence: 56%
See 2 more Smart Citations
“…Time here is seen to be linked with arsenic also indicate the oxidative dissolution of arsenic mineral which may again be consider to release of arsenic in ground water as a time variable parameter. The same phenomenon is endorsed by Fazal et al (2001).…”
Section: Hierarchical Cluster Analysissupporting
confidence: 56%
“…In West Bengal arsenic species in contaminated drinking water were found to be arsenate and arsenite in 1:1 ratio (De, 2008). Pyrite oxidation has been proven to be the most acceptable hypothesis to explain the occurrence of arsenic in ground level water (Fazal et al, 2001). Therefore, the occurrence of arsenic might be coupled with the presence of iron (Fe) in water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arsenic is one of the toxic environmental pollutants which has recently attract attention because of its chronic and epidemic effects on human health through widespread water and crop contamination due to the natural release of this toxic element from aquifer rocks in Bangladesh (Fazal et a., 2001;Smith et al, 2000;Ahmed, 2000;Hopenhayn, 2006), West Bengal, India (Chakraborti and Das, 1997;Banerjee, 2000). Geogenic contamination of arsenic in aquifer rocks has also been reported in Thailand (Visoottiviseth et al, 2002), Vietnam, Inner Mongolia, Greece, Hungary, USA, Ghana, Chile, Argentina and Mexico (O'Neill, 1995;Smedley and Kinniburgh, 2002).…”
mentioning
confidence: 99%
“…The toxicity of arsenic follows the order: Inorganic As (III) species > Organic As (III) species > Inorganic As (V) species > Organic As (V) species > Elemental Arsenic. Arsenite is 60 times more toxic than arsenate (Fazal et al, 2001a), and arsenopyrite has been identified as the prime source of As pollution in Bangladesh (Fazal et al, 2001b). Arsenic can be introduced to a groundwater system through various means, including surface water and precipitation as well as anthropogenic and naturally occurring sources (Urik et al, 2009;Reza and Singh, 2010).…”
Section: Introductionmentioning
confidence: 99%